New Evidence of King MḤDYS? - Agosti, Gianfranco; Bausi, Alessandro (Aethiopica, 2020)
The role assigned by the late antique poet Nonnus of Panopolis (mid-fifth century CE) to Modaios, king of the ‘Indians’, in a few passages of his huge poem Dionysiaca, suggests that the choice of the character may be attributable to a connection between the Greek name of the king (Μωδαῖος) and the somewhat enigmatic MḤDYS, a mid-fifth-century king of Aksum, known only from numismatic evidence. The hypothesis opens the way to further reflection on the role allusions to contemporary events play in Nonnus’s poem as an evidence of a precise awareness about Aksum in Late Antique Egypt.